Stress as a Possible Mechanism in Melanoma Progression - M. Sanzo; R. Colucci; M. Arunachalam; S. Berti; S. Moretti (Dermatology Research and Practice)
The incidence of melanoma, the most aggressive type of cutaneous malignant tumor, is currently on the rise. Treatment in advanced stages is still unsuccessful compared with other malignant tumors, thus it is important to indentify the key mechanisms responsible for melanoma progression and metastasis. Genetic and molecular components, in particular, that are up- or downregulated in melanoma cells, affect the invasive potential of melanoma. Another possible important cofactor highlighted by recent studies is chronic stress, involving environmental and psychological factors, which can be an important cofactor in not only cancer progression in general but also in melanoma spreading. The negative effects of chronic stress have been evaluated epidemiologically in patients with breast and prostate cancer. In particular, the effects of stress mediators, namely, catecholamines have been studied on various human malignancies, including melanoma and have highlighted a significant increase of progression-related molecules. As such, this could be the starting point for a new approach in the treatment of advanced melanoma, in which the negative effects of stress are reduced or blocked.